The Use of Code Switching and Code Meshing in Today's Youth Speech - Yules Sianipar; Gunawan Tambunsaribu (DIALEKTIKA: JURNAL BAHASA, SASTRA DAN BUDAYA, 2022)
Young people today tend to use informal language in communicating orally and in writing, in expressing themselves in front of their community or friends, but at the same time they will change their use of language into formal language when they interact with people whose position or position is above them, whether they realize it or not. The use of informal language in expressing themselves by young people is called "code-meshing", the change in the language used is called "code-switching". This research is qualitative research that uses "screenshot chat" of these students in their "WhatsApp" group and also in a private "chat" with researchers as research data, which later be classified as "code-switching" and also how they express themselves by using informal language which will later be classified as "code-meshing". The code-switching action taken is based on the understanding of the language that these students have, they understand not only Indonesian but also understand foreign languages ​​and their respective regional languages, not only the standard language they can use but also non-standard or non-standard languages. usually called 'slang' language they understand it. Code-meshing arises because of a sense of comfort in the way a speaker expresses it. This happens because they feel comfortable using words to express themselves that they still can't let go of.